Conselho escolar e gestão democrática : análise da participação dos conselheiros nas escolas municipais de São Carlos - Ramos, Renata Pierini (2013)
The primary objective of this dissertation is to investigate the main factors that affect the participation of school counselors in public schools in São Carlos / SP. To this end, we opted for conducting empirical research in order to produce and analyze data capable of providing greater concreteness to the arguments. Thus, in order to determine the research tools and the universe to be studied, techniques for the gathering, samplings, and analysis of data, were selected. For the gathering of data, a questionnaire was applied to Community Education Managers and school counselors. In order to determine the sample, we opted to cover fifty school units ensuring that all segments represented in the School Board answer the questionnaire. And finally, our analyzes were grounded on studies by authors who discuss the democratic management of public schools as a means of extending citizenship and guaranteeing the right of participation. Our preliminary results indicate that, power relationships present in the in interpersonal relationships, is the main factor that hinders the participation of counselors, followed by bureaucratic aspects, described as a subcategory due to the fact that they are related to the fundamental category mentioned above. In contrast, engagement and knowledge in the field are presented in the research as factors that facilitate the participation of counselors. Thus, the results highlight the need to formulate strategies to minimize the negative factors and leverage them to promote the participation of counselors at the municipal level.